Atmospheric mercury concentrations observed at ground-based monitoring sites globally distributed in the framework of the GMOS network - Sprovieri, Francesca; Pirrone, Nicola; Bencardino, Mariantonia; D'Amore, Francesco; Carbone, Francesco; Cinnirella, Sergio; Mannarino, Valentino; Landis, Matthew; Ebinghaus, Ralf; Weigelt, Andreas; Brunke, Ernst-Günther; Labuschagne, Casper; et al. (My University, 2016)
Long-term monitoring of data of ambient mercury (Hg) on a global scale to assess its emission, transport, atmospheric chemistry, and deposition processes is vital to understanding the impact of Hg pollution on the environment. The Global Mercury Observation System (GMOS) project was funded by the European Commission (http://www.gmos.eu) and started in November 2010 with the overall goal to develop a coordinated global observing system to monitor Hg on a global scale, including a large network of ground-based monitoring stations, ad hoc periodic oceanographic cruises and measurement flights in the lower and upper troposphere as well as in the lower stratosphere. To date, more than 40 ground-based monitoring sites constitute the global network covering many regions where little to no observational data were available before GMOS. This work presents atmospheric Hg concentrations recorded worldwide in the framework of the GMOS project (2010–2015), analyzing Hg measurement results in terms of temporal trends, seasonality and comparability within the network. Major findings highlighted in this paper include a clear gradient of Hg concentrations between the Northern and Southern hemispheres, confirming that the gradient observed is mostly driven by local and regional sources, which can be anthropogenic, natural or a combination of both.